Berkshire manual of style for international publishing - Berkshire Publishing Group; Gale Group (Great Barrington, Massachusettes Berkshire Pub. Group, 2012)
Provides a unique repository of guidelines, rules, and exceptions to rules, meditations and asides on writing and word use, behind-the-scenes anecdotes, and publishing lore.
Part 1. Copyeditor's manual -- Part 2. Author and reviewer guidelines -- Part 3. Berkshire Publishing Group in-house style guidelines -- Part 4. Berkshire Publishing Group general authority list -- Part 5. Internationalizing a publication.
Electronic reproduction.
Keywords: Authorship -- Style manuals; Electronic books